Analysis of Housing Affordability Stress (HAS) in Indonesia: Determinants and Influencing Condition - Jayadinata, Difa Haq; Rokhim, Rofikoh (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
Housing Affordability Stress (HAS) has become an increasingly critical issue in Indonesia, with housing costs rising faster than income growth. This issue is particularly concerning in urban areas, where living costs are significantly higher than in other regions. Although previous studies have explored factors influencing HAS, research in developing countries with low financial literacy levels remains limited. This study employs two research models to analyze HAS in Indonesia. The first model examines the effects of household size, homeownership status, and residential location on HAS, while the second model investigates the role of financial literacy. Utilizing data from the National Socioeconomic Survey (SUSENAS) and the National Survey on Financial Literacy and Inclusion (SNLIK), the research identifies significant relationships between these variables and HAS. The findings reveal that larger households tend to face lower levels of HAS, while renters and urban residents are more likely to experience higher housing stress. Financial literacy is also shown to significantly influence HAS. However, the context of residential location remains a critical factor, as urban households continue to experience higher HAS levels despite higher financial literacy compared to rural areas. These insights highlight the need for integrated approaches that combine financial literacy initiatives with location-specific housing policies. The study offers practical recommendations for policymakers to develop inclusive strategies that address housing affordability challenges while fostering economic resilience and well-being.